Healthcare Providers’ Knowledge, Attitude, and Practices Regarding Prevention of Mpox in Vietnam - Han Thi Ngoc Nguyen; Tap Van Nguyen; Khanh Van Tran; Hau Viet Nguyen; Lan Y Vo; Pham Le An; Tuan Diep Tran; Giao Huynh (SAGE Open)
The re-emergence of the mpox virus in the context of the COVID-19 pandemic is affecting people worldwide. This study aimed to investigate knowledge, attitude, and practice (KAP) toward mpox among healthcare providers in Vietnam. A cross-sectional study was conducted from August to October 2022 using a self-reported questionnaire based on the literature and the theoretical framework of the Health Belief Model. The association between practices and associated factors was investigated by performing multivariable logistic regression analysis. A total of 612 participants were included in the final statistical analysis. Amongst them, the rates of sufficient knowledge, positive attitude, and good practice regarding mpox were 54.4%, 36.8%, and 51.8%, respectively. Participants who were female and attended training about mpox were more likely to show higher good practices. Meanwhile, those who knew about mpox through social media were less likely to have good practices than their counterparts. Those with sufficient knowledge and a positive attitude were found to be associated with higher good practices. The findings showed low levels of KAP especially positive attitudes toward practice among healthcare providers. Educational interventions should be implemented to enhance KAP as well as emphasize the threat that emerging zoonotic diseases pose to community health.